2013
DOI: 10.1144/m38.19
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 19 Global Cambrian trilobite palaeobiogeography assessed using parsimony analysis of endemicity

Abstract: Palaeobiogeographical data on Cambrian trilobites obtained during the twentieth century are combined in this paper to evaluate palaeoceanographic links throughc.30 myr, once these arthropods biomineralized. Worldwide major tectonostratigraphic units are characterized at series intervals of Cambrian time and datasets of trilobite genera (629 for Cambrian Series 2, 965 for Cambrian Series 3, and 866 for the Furongian Series) are analysed using parsimony analysis of endemicity. Special attention is given to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 158 publications
(169 reference statements)
5
51
0
1
Order By: Relevance
“…Notably, recent detrital zircon studies have demonstrated that the Sauk Sequence resulting from the transgression of cratonic Laurentia was not initiated in west Texas (USA) until the Cambrian, significantly later than along its eastern and western margins (Spencer et al, 2014). The fact that the first benthic trilobites reflect geographic differentiation between the two continental masses, the olenellids in Laurentia and the redlichiids in Gondwana (Brasier, 1992;Fortey et al, 1996;Lieberman, 2003;Álvaro et al, 2013), suggests significant separation prior to the start of Cambrian Stage 3 (ca. 521 Ma; Fig.…”
Section: Growth Of the Iapetus Ocean Basinmentioning
confidence: 99%
“…Notably, recent detrital zircon studies have demonstrated that the Sauk Sequence resulting from the transgression of cratonic Laurentia was not initiated in west Texas (USA) until the Cambrian, significantly later than along its eastern and western margins (Spencer et al, 2014). The fact that the first benthic trilobites reflect geographic differentiation between the two continental masses, the olenellids in Laurentia and the redlichiids in Gondwana (Brasier, 1992;Fortey et al, 1996;Lieberman, 2003;Álvaro et al, 2013), suggests significant separation prior to the start of Cambrian Stage 3 (ca. 521 Ma; Fig.…”
Section: Growth Of the Iapetus Ocean Basinmentioning
confidence: 99%
“…Analysis of the palaeobiogeographical distribution of exotic trilobites at generic level clearly indicates that the assemblage shows the strongest affinities with East Gondwana (particularly its Australian -Antarctic -Chinese segment), Laurentia, Kazakhstania, and Siberia, that is palaeogeographic areas located in low-latitude positions (e.g., Cocks and Torsvik 2006;Álvaro et al 2013;Text-figs 8, 9). Interestingly, genera considered to be typical and/or most numerous in specific palaeogeographic areas also have a wide palaeogeographic distribution.…”
Section: Affinities Of the Exotic Trilobitesmentioning
confidence: 99%
“…Traditional biogeographic studies have commonly supported the existence of a Paradoxides realm as one of the most robust biogeographic units with a paradoxidid-solenopleurid-conocoryphid assemblage spreading throughout Avalonia, the Mediterranean and central-European areas, and Baltica (Álvaro and Vizcaïno, 2003;Álvaro et al, 2014), as well as deep-and cold-marine waters of various latitudes, including deep-water settings surrounding tropical Laurentia (Babcock, 1994a,b). Unfortunately, correlations across the Mediterranean and central-European areas are still debated, probably partly weakened by individual taxonomic considerations (Álvaro and Clausen, 2005;Geyer and Landing, 2004).…”
Section: Provisional Series 3 Stagementioning
confidence: 99%
“…Les études biogéographiques traditionnelles ont couramment soutenu l'existence d'un domaine à Paradoxides comme l'une des unités biogéographiques les plus robustes, avec un assemblage à paradoxidides-solenopleurides-conocoryphides se répartissant au travers de l'Avalonie, des zones européennes centrales et méditer-ranéennes et de la Baltique (Álvaro et Vizcaïno, 2003 ;Álvaro et al, 2014), ainsi que dans les eaux marines profondes et froides de diverses latitudes comme celles entourant le Laurentia tropical (Babcock, 1994a,b). Hélas, les corrélations au sein des zones méditerranéenne et de l'Europe centrale sont toujours débattues, probablement en partie fragilisées par des considérations taxonomiques individuelles (Álvaro and Clausen, 2005 ;Geyer et Landing, 2004).…”
Section: Série 3 éTage 5 Provisoiresunclassified